2017
DOI: 10.18632/oncotarget.22903
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of lncRNA SNHG1 indicates poor prognosis and promotes cell proliferation and metastasis of colorectal cancer by activation of the Wnt/β-catenin signaling pathway

Abstract: Recently, the lncRNA small nucleolar RNA host gene (SNHG1) has been exhibited to be upregulated, which plays a crucial role in the development and prognosis of several cancers. However, the role of the biology and clinical significance of SNHG1 in the tumorigenesis of colorectal cancer (CRC) has rarely been reported. In this work, we firstly found that SNHG1 expression levels were upregulated aberrantly in colorectal cancer tissues and colorectal cancer cell lines. By Kaplan-Meier survival analysis, patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…It is known that lncRNAs play functional roles in a series of steps during tumor development, and they may interact with DNA, RNA, protein and/or various combinations to act as important regulators of chromatin organization and transcriptional as well as posttranscriptional regulation . Recent studies indicate that the ncRNA SNHG1 plays important roles in tumor development, and have provided new insights into the biological activities of SNHG1 in tumors (including CRC) . However, the roles of lncRNAs in CRC tumorigenesis remain incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that lncRNAs play functional roles in a series of steps during tumor development, and they may interact with DNA, RNA, protein and/or various combinations to act as important regulators of chromatin organization and transcriptional as well as posttranscriptional regulation . Recent studies indicate that the ncRNA SNHG1 plays important roles in tumor development, and have provided new insights into the biological activities of SNHG1 in tumors (including CRC) . However, the roles of lncRNAs in CRC tumorigenesis remain incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…21 Recent studies indicate that the ncRNA SNHG1 | 2111 CRC). 22 However, the roles of lncRNAs in CRC tumorigenesis remain incompletely understood. The current study demonstrates that the oncogenic activity of SNHG1 in CRC is mediated through regulation of the miR-137/RICTOR axis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cyclin D1, c-Myc, MMP9, and MDR1 are several pivotal downstream targets of Wnt/β-catenin pathway which play important roles in tumor proliferation, migration, invasion, and chemoresistance. 27,28 Interestingly, our data revealed the positive correlations between GPC4 and above target genes (Supporting Information Figure S1). More importantly, our further investigations demonstrated that both the mRNA levels and the protein levels of these genes were downregulated upon knockdown of GPC4 ( Figure 7C,D).…”
Section: Regulation Genesmentioning
confidence: 59%
“…However, GPC4‐knockdown cells showed a reduced level of nuclear β‐catenin and an increased level of cytoplasmic β‐catenin when compared with control cells (Figure B). Furthermore, cyclin D1, c‐Myc, MMP9, and MDR1 are several pivotal downstream targets of Wnt/β‐catenin pathway which play important roles in tumor proliferation, migration, invasion, and chemoresistance . Interestingly, our data revealed the positive correlations between GPC4 and above target genes (Supporting Information Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Upon receiving the Wnt canonical ligand, β-catenin accumulates and is trans-localized to the nucleus where it binds to TCFs and triggers the expression of downstream target genes [20]. Numerous lncRNAs such as lncTCF7 and SNHG1 have been reported to regulate Wnt/β-catenin signaling [39,40], while none of these lncRNAs bind to β-catenin. Our data showed that LINC01197 sequesters β-catenin binding to TCF4 in PDAC cells and then inhibits Wnt/β-catenin signaling.…”
Section: Discussionmentioning
confidence: 99%